Opening Kailasanatha : the temple in Kanchipuram revealed in time and space - Kaimal, Padma Audrey (University of Washington Press, 2020)
Stone figures hardened by ascetic discipline and heroic effort face north in deep shadow. There they meet the gazes of the same gods and goddesses but with gentler bodies enacting grace, warmth, seduction, and marriage, drenched in sunlight, facing south. These figures adorn the eighth-century Kailasanatha temple complex in southeastern India, built by rulers who were both warriors and ascetics, engaged in the work of this world and in spiritual quests. They designed their temple as an exuberant visual feast to sustain both modes of being. 0In 'Opening Kailasanatha', Padma Kaimal deciphers the intentions of the monument's makers, reaching back across centuries to illuminate worldviews of the ancient Indic south. She reveals how circling the complex in a clockwise direction focuses the mind and spirit on worldly engagement; in a counterclockwise direction, on renunciation and ascetic practice. This pairing of highly charged, complementary pathways enabled devotees to grasp these counterpoised opportunities in their own listening, gazing, moving bodies. By focusing on the material form of the complex-the architecture, inscriptions, and sculptures, along with the spaces they carve out that guide light, shadow, sound, and footsteps-Kaimal offers insights that complement what surviving texts tell us about Shaiva Siddhanta ideas and practices, providing a rare opportunity to walk in the distant past.